The influence of size on cost behaviour associated with tactical and operational flexibility - Argilés Bosch, Josep Mª; García Blandón, Josep (Estudios de Economía, 2016)
This paper contributes with an empirical analysis, using a sample of farms, on the influence of size on cost behaviour under operational and tactical flexibility. Results indicate that small farms behave advantageously with respect to biggest farms in situations of operational and tactical flexibility. On the one hand, the increase in indirect costs with product diversification is higher in bigger farms than in smaller. On the other hand, while most farms are flexible enough to avoid cost stickiness, the biggest face considerable rigidities in downsizing indirect costs when activity decreases.